Nusantara Wisdom for CSR Concept - Rayyani, Wa Ode; Dyastiarini, Astri; Arif, Muhammad Faisal; Syarifuddin, Safria; Hanafi, Kartini; Damayanti, Ratna Ayu (AIBPM Publisher, 2023)
This writing aims to propose a concept of Corporate Social Responsibility (CSR) based on the wisdom of the Bugis-Makassar community, particularly drawing inspiration from the values of Sipakalebbi, Sipakatau, and Sipakainge nusantara. We use a three-step method consisting of content analysis through document review. The reviewed documents include news from trusted online media sources and CSR reports from various companies, which are analyzed to understand the flow of CSR funds. The third step involves extracting the values of Bugis-Makassar Sipakalebbi, Sipakatau, and Sipakainge nusantara wisdom as a framework for a just CSR concept. We found that a CSR concept based on these three Bugis-Makassar values can serve as a compass and character builder for corporate CSR initiatives in Indonesia. These three values are expected to uphold justice for society and the environment. Corporate Social Responsibility (CSR) has become an integral part of modern business practices, aimed at promoting positive impacts on society and the environment. In the context of Indonesia, this research proposes a CSR concept rooted in the wisdom of the Bugis-Makassar community, specifically drawing inspiration from the values of Sipakalebbi, Sipakatau, and Sipakainge.